Zeus Theos Megistos en Segobriga - Abascal Palazón, Juan Manuel; Alföldy, Géza (Archivo español de arqueología, 1998)
A Greek inscription found during excavations undertaken at Segobriga (Saelices, Cuenca) in 1995 provides a dedication to Zeus Theos Megistos by C. lulius Siluanus. The connection between the city and C. lulius Siluanus Melanio, the procurator of mines who was probably responsible for the dedication, is the subject of this article.
Gesehen am 14.02.2024